Variants in STXBP3 are Associated with Very Early Onset Inflammatory Bowel Disease, Bilateral Sensorineural Hearing Loss and Immune Dysregulation. (23rd April 2021) - Ouahed, Jodie; Kelsen, Judith R; Spessott, Waldo A; Kooshesh, Kameron; Sanmillan, Maria L; Dawany, Noor; Sullivan, Kathleen E; Hamilton, Kathryn E; Slowik, Voytek; Nejentsev, Sergey; Neves, João Farela; Flores, Helena; et al.
Abstract: Background and Aims: Very early onset inflammatory bowel disease [VEOIBD] is characterized by intestinal inflammation affecting infants and children less than 6 years of age. To date, over 60 monogenic aetiologies of VEOIBD have been identified, many characterized by highly penetrant recessive or dominant variants in underlying immune and/or epithelial pathways. We sought to identify the genetic cause of VEOIBD in a subset of patients with a unique clinical presentation. Methods: Whole exome sequencing was performed on five families with ten patients who presented with a similar constellation of symptoms including medically refractory infantile-onset IBD, bilateral sensorineural hearing loss and, in the majority, recurrent infections. Genetic aetiologies of VEOIBD were assessed and Sanger sequencing was performed to confirm novel genetic findings. Western analysis on peripheral blood mononuclear cells and functional studies with epithelial cell lines were employed. Results: In each of the ten patients, we identified damaging heterozygous or biallelic variants in the Syntaxin-Binding Protein 3 gene [ STXBP3 ], a protein known to regulate intracellular vesicular trafficking in the syntaxin-binding protein family of molecules, but not associated to date with either VEOIBD or sensorineural hearing loss. These mutations interfere with either intron splicing or protein stability and lead to reduced STXBP3 protein expression. Knock-down of STXBP3 in CaCo2 cells resulted in defects in cell polarity. Conclusion: Overall, we describe a novel genetic syndrome and identify a critical role for STXBP3 in VEOIBD, sensorineural hearing loss and immune dysregulation.